2021
DOI: 10.1002/mmce.22620
|View full text |Cite
|
Sign up to set email alerts
|

The design of a multi‐band bionic antenna for mobile terminals

Abstract: This article proposes and designs a multi-band antenna that imitates banana leaves structurally. The edge structure of the antenna radiator is a mirrorsymmetrical trapezoid, and four patches of different sizes are used as leaf veins inside. The feeding mode is coplanar waveguide feeding with a trapezoidal structure. The electromagnetic simulation software HFSS is used for antenna modeling and parameter optimization. The test results show that the antenna can cover 0.79 to 3.18 GHz, 3.29 to 3.98 GHz, and 4.98 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The regular and simple structure is also easy for simulation calculation and physical processing. 24,25 Therefore, antler structure is chosen as the bionic model.…”
Section: Design and Structure Of Antler-like Antennamentioning
confidence: 99%
“…The regular and simple structure is also easy for simulation calculation and physical processing. 24,25 Therefore, antler structure is chosen as the bionic model.…”
Section: Design and Structure Of Antler-like Antennamentioning
confidence: 99%
“…The working principle and performance of antennas are similar to those of the organisms in nature; hence, by imitating the structure of organisms to design the geometric structure of antennas, good performance can be obtained [5,6]. Examples include the use of plane-opposed Vivaldi miniature antennas inspired by natural ferns [7], a broadband antenna that simulates the shape of a ginkgo leaf [8], multiband antennas imitating banana leaves [9], and slot-shaped antennas imitating the shadow of butterfly wings under the sun [10,11]. The antenna can change the available frequency band from single frequency to dual frequency by adding semicircular arc branches to the circular monopole to form a "C + O" structure [12].…”
Section: Introductionmentioning
confidence: 99%
“…Self-similarity in fractal antennas permits the achievement of similar surface current distributions in different planes as well as multifrequency characteristics; space filling enables the increase of the antenna electrical length [15,16]. Furthermore, it has been shown that the frequency band of antennas can be increased by adding branches and slits [17,18]. In order to reduce the size of antennas, it is important to note that the size of the dielectric resonant antenna (DRA) is proportional to the parameter λ/ε 1/2 r .…”
Section: Introductionmentioning
confidence: 99%